PENGEMBANGAN BAHAN AJAR MATERI BILANGAN BULAT BERBASIS PMRI MENGGUNAKAN KONTEKS WISATA MUSI RAWAS - Dewi, Rismala; Sukasno, Sukasno (Universitas Bhinneka PGRI, 2024)
This research emphasizes teaching materials that are conceptual in nature and do not use a context that is close to students. The research objective is to produce PMRI-based teaching material products about integers. The research subjects were class III students at SD Negeri 31 Lubuklinggau. The research design uses the ADDIE research and development model with 5 stages, namely analysis, design, development, implementation and evaluation. Data collection uses interviews and questionnaires. Validation and practicality questionnaire instruments are used to measure the validity and practicality of PMRI-based teaching materials. Based on the results of the validity data analysis carried out by the three experts, their respective scores were obtained, namely media experts got a score of 0.88, language experts got a score of 0.83 and material experts got a score of 0.75. The results of the analysis of the small group practicality questionnaire data obtained an average score of 89% and the teacher response practicality questionnaire data obtained an average score of 95%. Thus, it can be concluded that the PMRI-based integer teaching materials using the Musi Rawas tourism context are valid and practical so that they can be declared suitable for use.